Comparison of methods for measuring and assessing carbon stocks and carbon stock changes in terrestrial carbon pools. How do the accuracy and precision of current methods compare?: a systematic review protocol - Petrokofsky, G.; Kanamaru, Hideki; Achard, F.; Goetz, S.J; Joosten, H.; Holmgren, P; Lehtonen, A; Menton, M.; Pullin, A.S.; Wattenbach, M. (Springer, 2012)
Background: Climate change and high rates of global carbon emissions have focussed attention on the need for high-quality monitoring systems to assess how much carbon is present in terrestrial systems and how these change over time. The choice of system to adopt should be guided by good science. There is a growing body of scientific and technical information on ground-based and remote sensing methods of carbon measurement. The adequacy and comparability of these different systems have not been fully evaluated.